Biblical Discourse on the Theological and Practical Significance of the Lord’s Supper - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
This study explores the theological and practical significance of the Lord’s Supper within its soteriological, koinonia, missional, and eschatological dimensions. Employing biblical analysis, theological literature review, and field observations, this research offers a profound understanding of the Lord’s Supper and its application in contemporary church practices. The integrative approach adopted combines both theological and practical aspects, affirming that the Lord’s Supper is not merely an institutional rite but a command of Christ, rich in meaning. The findings reveal that the Lord’s Supper serves as a reminder of Christ’s sacrifice while also strengthening the eschatological hope of the Christian community. This study underscores the importance of eschatological understanding in worship and daily life, contributing to the development of church practices that are more mission-oriented and eschatologically focused.